Britain And The British - Ganeri, Anita (London Franklin Watts, 1993)
Offers an insight into Britain and the lives of the British people. It includes information about geography, language and literature, science and math, history, and the arts.
Include Color Illustration, and Index
Keywords: Great Britain -- Intellectual life -- Travel